PENGARUH CEKAMAN AIR TERHADAP MUTU SIMPLISIA PEGAGAN (Centella asiatica L) - MONO RAHARDJO; ROSITA SMD; RATNA FATHAN; SUD1ARTO SUD1ARTO (Pusat Penelitian dan Pengembangan Perkebunan, 1999)
Effect of water stress on the quality of Centella asiatica L. simplisiaResearch on the effect of water stress on Centella asiatica L. was done at the Research Institute for Spice and Medicinal Cops, Bogor. fom January 1997 to March 1998. The objective of the research was to increase the quality of C asiatica L simplisia. Six treatments of water stress were applied based on the percentages of field capacity : (1) 100%, (2) 90%, (3) 80%. (4) 70%. (5) 60%, and (6) 50%. A randomized block design with five replications was used, and each replication in one treatment contained four polybags. Each polybag contained 9.25 kg of soil mixed with 750 g of dung, and 3 g of urea, TSP, and KCI respectively. Three plants o/C. asiatica L. fom Banjaran Bandung wee planted in each polybag. The teatment of water stress was applied one month after planting, then the plants were harvested al two months old. Observation of biomass production included : leaf number, leaf area, fresh and dry weight of leaves, petiole, and stem. Observation on the quality of simplisia included the contents of the contents of asiaticoside acid, asiatic acid, and madecasic acid. The result indicated that water stress showed negative correlation with biomass accumulation. Inceasing 1% of water stress decreased 191 mg of biomass accumulation. Application of water stess could inceased the quality of C*. asiatica L. simplisia. The optimum of asiaticoside acid at the treatment of 53.9% of field capacity was 3.56%, asiatic acid at the treatment of 65.1% of field capacity was 1.42%. and madecasic acid at the treatment of 68.5% of field capacity was 1.76%.